Studies on the ecology of Bulinus globosus snails: Evidence against burrowing into the soil during the dry season - Hang, De-Rong; Feng, Yun; Zhang, Jian-Feng; Wang, Yun-Hua; Zhang, Biao; Juma, Seleh; Sleiman, Mchanga Mohd; Yang, Kun (Frontiers in Environmental Science, 2022)
Background Bulinus globosus snail was the intermediate host of schistosome hematobium and hard to be found during the dry season. This study aimed to understand the vertical distribution of B. globosus in desiccated and re-hydrated soils and provide evidence that whether snails can drill into the soil for summer. Methods Four laboratory/field experiments were designed to study the downward movement of the snails in desiccated soils or upward movement in re-watered soils. In experiment 1, aquaria containing snails on the soil surface were placed in an outdoor environment to desiccate naturally. Snails were then retrieved by different soil layers. In experiment 2, snails on the soil surface were covered with an extra 5cm layer of soil and 4cm layer of water. The snail position and living rate were checked on the 1st, 3rd, 5th, 7th, 9th day. In experiment 3, a seasonal ditch was selected in the field. After the soil in the ditch was naturally desiccated, 1cm, 1-3cm, 3-5cm, 5-10cm depth of soil layers were screened to retrieve snails. In experiment 4, after the above ditch was naturally re-watered, snails were checked in the surface water once a week for five weeks. Results At the end of experiment 1, all the snails were only found at the soil surface. At the end of experiment 2, snails were found neither within nor on top of the 4cm layer of extra mud. At the end of experiment 3, 96.92% of snails remained on the soil surface. 2.77% of living snails were found in the mud crack within 1-5cm depth. In experiment 4, no snails were found above the soil surface after the experimental field was naturally re-watered. Conclusions B. globosus snails don’t initially move downward into the soil during the dry season or upward to the soil surface after being re-watered.